Cloud response to summer temperatures in Fennoscandia over the last thousand years - Gagen, M.; Zorita, E.; McCarroll, D.; Young, G.H.F.; Grudd, H.; Jalkanen, R.; Loader, N.J.; Robertson, I.; Kirchhefer, A. (Geophysical Research Letters, 2011)
Cloud cover is one of the most important factors controlling the radiation balance of the Earth. The response of cloud cover to increasing global temperatures represents the largest uncertainty in model estimates of future climate because the cloud response to temperature is not well-constrained. Here we present the first regional reconstruction of summer sunshine over the past millennium, based on the stable carbon isotope ratios of pine treerings from Fennoscandia. Comparison with the regional temperature evolution reveals the Little Ice Age (LIA) to have been sunny, with cloudy conditions in the warmest periods of the Medieval at this site. A negative shortwave cloud feedback is indicated at high latitude. A millennial climate simulation suggests that regionally low temperatures during the LIA were mostly maintained by a weaker greenhouse effect due to lower humidity. Simulations of future climate that display a negative shortwave cloud feedback for high-latitudes are consistent with our proxy interpretation.